Systematic review and classification of: The VIP Partnership Program - Havik, Trude; Rye, Marte (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2023)
Background: The VIP Partnership Program is a health promoting and universal preventive program, developed to facilitate a better transition from lower to upper secondary school (and from primary to lower secondary school) and to promote a good learning environment. The VIP Partnership Program is developed and owned by Vestre Viken Hospital Trust/VIP Mental health in school and financed by the Norwegian Directorate of Health as part of the subsidy scheme “Mental Health in School”.Methods: This review is based on a systematic literature search in the databases Embase, Medline, Psyinfo, NORART, Cochrane, Cristin, NORA, SCOPUS and SweMed. International databases on evidence have also been searched, as well as information about the intervention from the program provider. Results from literature searches and the other information obtained were reviewed to identify Nordic effect studies, international systematic reviews and eventually other Norwegian studies of the intervention.Results: The results include an assessment of the programs description, present efficacy study, research methodological quality and implementation quality. The VIP Partnership Program is considered well described and has a broad professional-based framework, while no specified theoretical foundation. The intervention offers some implementation support by offering information meetings and three-hours training. Two Norwegian efficacy studies have been conducted, both with a quasi-experimental design. The first study indicates a significant improvement for schools using the VIP Partnership Program on one outcome variable - social classroom environment, as compared to control schools not implementing the program. The effect was small, and as the VIP Partnership Program was introduced in some of the schools prior to baseline and the nesting in data was ignored in the analyses, the findings are dubious. The second study showed positive outcomes at post-test for happiness and joint depression/anxiety symptoms among students with no or low anxiety at baseline, but not among student with high anxiety. No significant effects were found at six-months follow-up. There were no significant improvements on loneliness.More studies with a stronger design and analytical approach, and several relevant outcome variables tested are needed to draw any conclusions on program effects in lower and upper secondary schools. In addition, the theoretical rationale for the program should be pointed and justified, and the implementation strategy further developed.Conclusion: The VIP Partnership Program is classified at evidence level 3 – measures with some documen-tation of effect.
Keywords: Universal Preventive Program; Learning Environment; Secondary School; High School; School Program